PENGEMBANGAN MODUL BERPIKIR KOMPUTASIONAL BERBANTUAN SCRATCH PADA MATERI EKOSISTEM KELAS V SEKOLAH DASAR - Novi Ramdhani; Akhmad Nugraha; Muhammad Rijal Wahid Muharram (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This research was conducted to produce a computational thinking module using scratch ecosystem material for class V elementary schools. The method applied in this research is Educational Design Research (EDR). The research subjects consisted of 30 class V-A students at SDN 7 Ciamis and 15 class V students at SDN 2 Sindangsari. Data collection techniques include validation sheets and student response questionnaires after using the module. The validation results from 2 validators received an average score of 83.33% which shows decent qualifications. In the first stage of testing, the questionnaire results showed a percentage of 89.17% in the very feasible category. Meanwhile, the second stage of the trial showed a percentage of 91.87% in the very feasible category. Therefore, the computational thinking module that has been developed can be used as a learning tool for computational thinking in grade V elementary school ecosystem material.